Oviposition Behavior of Scirpophaga incertulas, the Yellow Stemborer (Lepidoptera: Crambidae) in A Non-Choice Study - Yin, Hui Cheok; Kuok, Freddy San Yeo; Yee, Ling Chong (UPM Press, 2019)
Scirpophaga incertulas, or the yellow stemborer, is a dominant paddy pest in Asia and contributes to great yield loss in paddy cultivation. Breeding paddy varieties that are resistant to yellow stemborer is an eco-friendly alternative for managing this pest rather than using hazardous chemical insecticides. In this non-choice study, the oviposition behaviour of female yellow stemborers on three different local Sarawak paddy landraces was observed. The number and size of egg masses found on the three local paddy landraces, namely Bajong, Bubok, and Bario, were similar. In general, the yellow stemborers of this study preferred to oviposit on the leaves instead of stems. On leaves, the number of egg masses oviposited on the abaxial side and adaxial side of leaves was comparable. Based on this preliminary data, the three local paddy landraces may not be good candidates in a program that resists towards yellow stemborers.